Perlindungan Kebebasan Beragama Dalam Hukum Internasional Terkait Kasus Pembakaran Al Quran Serta Pelanggaran Terhadap Hak Beragama Menurut Norma – Norma Hukum Internasional - Andi, Rafliyandi; Sutrisno, Andri (Program Studi Kesejahteraan Sosial Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Ar-Raniry, 2024)
The incident of Quran burning that occurred in European countries has been quite massive, such as what happened recently in Sweden, which has caused strong protests and diplomatic rifts with Muslim-majority countries. The method used for this research is normative juridical with a qualitative approach by collecting and using information related to the problems that describe and analyze how freedom of religion is part of human rights. The Organization of Islamic Cooperation (OIC) responded to the burning of the Qur'an by calling for a meeting to discuss the implications of this event so that there would not be widespread repercussions. The provocative act of burning the Qur'an, which angered Islamic countries, should form more specific binding international rules regarding the holy book, not only the Qur'an, but for all holy books.